Elastomeric biocomposite of silver-containing mesoporous bioactive glass and poly(1,8-octanediol citrate): Physiochemistry and in vitro antibacterial capacity in tissue engineering applications - Pourshahrestani, Sara; Zeimaran, Ehsan; Kadri, Nahrizul Adib; Gargiulo, Nicola; Jindal, Hassan Mahmood; Hasikin, Khairunnisa; Naveen, Sangeetha Vasudevaraj; Sekaran, Shamala Devi; Kamarul, Tunku (Elsevier, 2019)
A novel series of silver-doped mesoporous bioactive glass/poly(1,8-octanediol citrate) (AgMBG/POC) elastomeric biocomposite scaffolds were successfully constructed by a salt-leaching technique for the first time and the effect of inclusion of different AgMBG contents (5, 10, and 20 wt%) on physicochemical and biological properties of pure POC elastomer was evaluated. Results indicated that AgMBG particles were uniformly dispersed in the POC matrix and increasing the AgMBG concentration into POC matrix up to 20 wt% enhanced thermal behaviour, mechanical properties and water uptake ability of the composite scaffolds compared to those from POC. The 20%AgMBG/POC additionally showed higher degradation rate in Tris(hydroxymethyl)-aminomethane–HCl (Tris–HCl) compared with pure POC and lost about 26% of its initial weight after soaking for 28 days. The AgMBG phase incorporation also significantly endowed the resulting composite scaffolds with efficient antibacterial properties against Escherichia coli and Staphylococcus aureus bacteria while preserving their favorable biocompatibility with soft tissue cells (i.e., human dermal fibroblast cells). Taken together, our results suggest that the synergistic effect of both AgMBG and POC make these newly designed AgMBG/POC composite scaffold an attractive candidate for soft tissue engineering applications. © 2019 Elsevier B.V.